Estrategias de crianza de familias monoparentales y su efecto en la autoestima de los hijos adolescentes. - Chimbolema Arias, Liliana Guadalupe (2025)
: Parenting patterns have an essential impact on the healthy development of adolescents since they transmit values, ways of thinking, and acting that will impact their future. During this period, selfesteem plays a fundamental role, as adolescents tend to make self-evaluation judgments based on the messages and responses they receive from their family and social environment. Considering that it is a stage of vulnerability for adolescents searching for their identity. The study's main objective was to analyze the effect of parenting strategies used in single-parent families on the development of self-esteem in adolescent children. It is bibliographic research since it focuses on collecting, analyzing, and synthesizing previous studies, with a total sample of 21 articles. Several sources, such as scientific articles from repositories such as Web of Science, PubMed, Dialnet, Scielo, and Scopus, were used. Based on a descriptive approach, articles were selected through a non-probabilistic purposive sampling. Techniques such as the review card, the prism method, and the CRF-QS instrument were used. The results showed that adolescents in single-parent families have low levels of self-esteem, and that the authoritarian and negligent style prevails in these homes, which allowed us to identify a correlation between both study variables. Single-parent or dysfunctional families present greater dysfunctionality in the bond and communication with their children, which may be associated with the presence of emotional maladjustments in their children.